2019
DOI: 10.1029/2019gb006264
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Predictions and Associated Uncertainty of Annual Soil Respiration at the Global Scale

Abstract: Soil respiration (Rs), the soil‐to‐atmosphere CO2 flux produced by microbes and plant roots, is a critical but uncertain component of the global carbon cycle. Our current understanding of the variability and dynamics is limited by the coarse spatial resolution of existing estimates. We predicted annual Rs and associated uncertainty across the world at 1‐km resolution using a quantile regression forest algorithm trained with observations from the global Soil Respiration Database spanning from 1961 to 2011. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
108
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(156 citation statements)
references
References 68 publications
16
108
2
Order By: Relevance
“…and ≈500 for heterotrophic respiration many peer-reviewed literature in the SRDB 4.0 database (Bond-Lamberty, 2018) allows regional and global up-scaling of this flux for averages over a given period (Hashimoto et al, 2015;Konings et al, 2019;Warner et al, 2019) or with annual variations (Yao et al 2020) that can be used for RECCAP2.…”
Section: Carbon Emissions From Soil Heterotrophic Respiration Rmentioning
confidence: 99%
“…and ≈500 for heterotrophic respiration many peer-reviewed literature in the SRDB 4.0 database (Bond-Lamberty, 2018) allows regional and global up-scaling of this flux for averages over a given period (Hashimoto et al, 2015;Konings et al, 2019;Warner et al, 2019) or with annual variations (Yao et al 2020) that can be used for RECCAP2.…”
Section: Carbon Emissions From Soil Heterotrophic Respiration Rmentioning
confidence: 99%
“…The updated SRDB-V5 provides opportunities for constraining global RS estimates in the future. Currently, estimated global RS ranged from 68-101 Pg C yr -1 , with many uncertainties associated with measurements and propagation of errors evident when upscaling site-specific RS measurements to regional and global scales (Bond-Lamberty and Thomson, 2010b;Jian et al, 2018aJian et al, , 2018bRaich et al, 2002;Raich and Potter, 1995;Raich and Schlesinger, 1992;Warner et al, 2019). For example, RS has been usually measured during daylight hours,…”
mentioning
confidence: 99%
“…et al (2018b) found that how RS responds to temperature is significantly different among climate regions, and therefore climate-specific models may be more appropriate than a global single model to estimate global RS. Alternatively, machine learning approaches that account for non-linearity and multiple potential combinations of environmental factors have been used to estimate global RS (Warner et al, 2019). SRDB-V5 also significantly increased the RS sample size, and analyses could be conducted to test whether the increasing sample size of RS helps 315 reduce uncertainty when upscaling from site to global scale RS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For soil respiration, including both autotrophic respiration by roots and heterotrophic respiration, some global datasets have been developed (Bond-Lamberty and Thomson, 2010;Hashimoto et al, 2015). Recently efforts to estimate heterotrophic respiration have also been made using machine learning techniques, Tang et al (2019) and Warner et al (2019) being the first attempts. The separation of heterotrophic respiration from the autotrophic respiration remains still a challenge and in these two studies it has been done at yearly scales.…”
Section: Introductionmentioning
confidence: 99%